Pecalang Simbol Kekuatan Budaya Bali - Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI (SOROT), 2014)
ABSTRACT Pecalang represent the traditional security group owning fundamental duty to take care of the security and fluency of ritual and custom in region. Generally pecalang using black clothes completely, udeng (fastener lead the), black and white colour cloth (poleng), and bring the keris assumed dreadful, making Bali society shy at to deal by pecalang. This phenomenon use interactionalism symbolic theory from George Herbert Ad studying to hit how one can have interaction with the others do not only use the communications verbal but also with the communications non verbal, example by using symbol. Keywords: pecalang, Balinese culture strength, symbolic intercationalism